Antioxidant and anti-inflammatory activities of selected Chinese medicinal plants and their relation with antioxidant content - Ravipati Anjaneya S; Zhang Lin; Koyyalamudi Sundar; Jeong Sang; Reddy Narsimha; Bartlett John; Smith Paul T; Shanmugam Kirubakaran; Münch Gerald; Wu Ming; Satyanarayanan Manavalan; Vysetti Balaram (BMC, 2012)
Abstract Background The main aim of this study is to evaluate the antioxidant and anti-inflammatory properties of forty four traditional Chinese medicinal herbal extracts and to examine these activities in relation to their antioxidant content. Methods The antioxidant activities were investigated using DPPH radical scavenging method and yeast model. The anti-inflammatory properties of the herbal extracts were evaluated by measuring their ability to inhibit the production of nitric oxide and TNF-α in RAW 264.7 macrophages activated by LPS and IFN- γ, respectively. The cytotoxic effects of the herbal extracts were determined by Alomar Blue assay by measuring cell viability. In order to understand the variation of antioxidant activities of herbal extracts with their antioxidant contents, the total phenolics, total flavonoids and trace metal (Mg, Mn, Cu, Zn, Se and Mo) quantities were estimated and a correlation analysis was carried out. Results Results of this study show that significant levels of phenolics, flavonoids and trace metal contents were found in Ligustrum lucidum, Paeonia suffuticosa, Salvia miltiorrhiza, Sanguisorba officinalis, Spatholobus suberectus, Tussilago farfara and Uncaria rhyncophylla, which correlated well with their antioxidant and anti-inflammatory activities. Some of the plants displayed high antioxidant and anti-inflammatory activities but contained low levels of phenolics and flavonoids. Interestingly, these plants contained significant levels of trace metals (such as Zn, Mg and Se) which are likely to be responsible for their activities. Conclusions The results indicate that the phenolics, flavonoids and trace metals play an important role in the antioxidant activities of medicinal plants. Many of the plants studied here have been identified as potential sources of new antioxidant compounds.